Assessing L. donovani Skin Parasite Load: A Proof of Concept Study of a Microbiopsy Device in an Indian Setting - Cloots, Kristien; Singh, Om Prakash; Singh, Abhishek Kumar; Van der Auwera, Gert; Kumar, Prashant; Gedda, Mallikarjuna Rao; Rai, Tulika Kumari; Hasker, Epco; Sundar, Shyam; Boelaert, Marleen (Frontiers in Cellular and Infection Microbiology, 2021)
Background In the endgame of the elimination initiative of visceral leishmaniasis (VL) on the Indian subcontinent, one of the main questions remaining is whether asymptomatically infected individuals also contribute to transmission. We piloted a minimally invasive microbiopsy device that could help answer this question. While the potential of this device has been previously illustrated in Ethiopia, no such information is available for the setting of the Indian subcontinent. In this proof of concept study we aimed to assess 1) to what extent skin parasite load obtained with the new microbiopsy device correlates with disease status, 2) to what extent skin parasite load correlates with blood parasite load in the same subject, and 3) to what extent the skin parasite load obtained from different sampling sites on the body correlates with one another. Methods We performed a pilot study in Bihar, India, including 29 VL patients, 28 PKDL patients, 94 asymptomatically infected individuals, 22 endemic controls (EC), and 28 non-endemic controls (NEC). Presence of infection with L. donovani in the blood was assessed using Direct Agglutination Test, rK39 ELISA, Whole Blood Analysis measuring IFN-γ and qPCR. A skin sample was collected with the microbiopsy device on two different locations on the body. PKDL patients provided a third skin sample from the edge of a PKDL lesion. Parasite load in the skin was measured by qPCR. Findings We found a clear correlation between the skin parasite load obtained with the microbiopsy device and disease status, with both higher skin parasite loads and higher proportions of positive skin samples in VL and PKDL patients compared to asymptomatics, EC, and NEC. No clear correlation between skin parasite load and blood parasite load was found, but a moderate correlation was present between the skin parasite load in arm and neck samples. In addition, we found four positive skin samples among asymptomatic individuals, and 85% of PKDL lesions tested positive using this microbiopsy device. Conclusions In line with previous pilot studies, our results from an Indian setting suggest that the microbiopsy device provides a promising tool to measure skin parasite load, and – if validated by xenodiagnosis studies – could facilitate much needed larger scale studies on infectiousness of human subgroups. In addition, we advocate further evaluation of this device as a diagnostic tool for PKDL.